Analysis of screen adaptation form novel to film “Merindu Cahaya De Amstel” - Maulida Intan Nafis; Trie Utari Dewi (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research aims to describe the process of adaptation from the novel Merindu Cahaya De Amstel by Arumi Ekowati to the film Merindu Cahaya De Amstel directed by Hadrah Daeng Ratu. This study used a descriptive qualitative method to describe the forms of adaptation in the novel and the film. The data sources were the novel and the film. The data were collected through note-taking techniques. The presentation of the analysis results used descriptive analysis techniques with three steps: describing, analyzing the data, and concluding the results. The results of this study showed that there was an adaptation process from the novel to the film, with a total of 15 data found consisting of 3 data on the plot, 7 data on the setting, and 5 data on the characters. Eight data additions were found, consisting of 2 data on the plot, 4 data on the setting, and 2 data on the characters. Then, five data changes were found, consisting of 2 data on the plot, 1 data on the setting, and 2 data on the characters. Thus, the most prominent process of adaptation from the overall data in this study was condensation.